ARTIST, MYTH AND METAPHOR. ABOUT “TREŚĆ UCZUCIOWA REWOLUCJI” BY ANDRZEJ WRÓBLEWSKI - Nowicka, Daria (Porównania, 2019)
This article focuses on the presence of mythological imagination in the work of one of the greatest post-war painters. The author defines the myth present in the works of Andrzej Wróblewski created in the 1940s and 1950s. The author presents three possible ways of understanding the myth: the myth of Orpheus, the myth of a lonely artist and the myth of a new cosmos. The author also discusses other problems: the status of his paintings in contemporary criticism, the reverse of artistic biography and languages of modernism from the 1950s.